CURRENT AND EMERGING USES OF PHOSPHODIESTERASE 5 INHIBITORS. - RAVINDRA S.BEEDIMANI; BHUVANESHWARI KALMATH (International Journal of Pharma and Bio Sciences, 2014)
Phosphodiesterase 5 (PDE5) is a key enzyme involved in the regulation of cGMPspecific signaling pathways in normal physiological processes such as smooth muscle contraction and relaxation. Initially, PDE5 inhibitors were developed as potential antianginal agents, but early clinical results were disappointing and the focus of these drugs moved to the treatment of Erectile Dysfunction (ED) based on the findings that nitric oxide and cyclic guanosine monophosphate were important mediators of penile erection. The overall goal of this review is to provide a comprehensive understanding of the current and potential therapeutic roles of the PDE5 enzyme inhibitors. Novel PDE5 inhibitors are highly selective for the PDE5 isoenzyme, and this may translate into potential novel indications and fewer adverse systemic effects. Larger scale, well designed clinical trials are needed to ascertain the safety, efficacy and costeffectiveness of PDE5 inhibitors in the future treatment of urological, cardiovascular, gastrointestinal, and central nervous system disorders.